Screening and follow up assessment in three cases of auditory neuropathy. Issue 1 (1st January 2003) - Dunkley, C; Farnsworth, A; Mason, S; Dodd, M; Gibbin, K
Abstract : Three children with auditory neuropathy are described. Two were detected via a targeted neonatal hearing screening programme based on auditory brain stem response testing, and one via the routine Health Visitor Distraction Test. Auditory neuropathy is an important but poorly understood disorder which has implications on planning future hearing screening policy and management of hearing impairment.